An investigation of the carbon nanotube – Lipid interface and its impact upon pulmonary surfactant lipid function. (July 2015) - Melbourne, Jodie; Clancy, Adam; Seiffert, Joanna; Skepper, Jeremy; Tetley, Teresa D.; Shaffer, Milo S.P.; Porter, Alexandra
Abstract: Multiwalled carbon nanotubes (MWCNTs) are now synthesized on a large scale, increasing the risk of occupational inhalation. However, little is known of the MWCNT-pulmonary surfactant (PS) interface and its effect on PS functionality. The Langmuir–Blodgett trough was used to evaluate the impact of MWCNTs on fundamental properties of PS lipids which influence PS function, i.e. compression resistance and maximum obtainable pressure. Changes were found to be MWCNT length-dependent. 'Short' MWCNTs (1.1 μm, SD = 0.61) penetrated the lipid film, reducing the maximum interfacial film pressure by 10 mN/m (14%) in dipalmitoylphosphatidylcholine (DPPC) and PS, at an interfacial MWCNT-PS lipid mass ratio range of 50:1 to 1:1. 'Long' commercial MWCNTs (2.1 μm, SD = 1.2) caused compression resistance at the same mass loadings. 'Very long' MWCNTs (35 μm, SD = 19) sequestered DPPC and were squeezed out of the DPPC film. High resolution transmission electron microscopy revealed that all MWCNT morphologies formed DPPC coronas with ordered arrangements. These results provide insight into how nanoparticle aspect ratio affects the interaction mechanisms with PS, in its near-native state at the air–water interface.